PENINGKATKAN MINAT BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENJASKES MELALUI PENERAPAN METODE PEMBELAJARAN DEMONSTRASI DI KELAS V SDN 04 SUNGAI LIMAU - Mulyani Mulyani (STKIP Pesisir Selatan, 2019)
Based on the learning process of Grade V students of SDN 04 Sungai Limau in the learning process, it was found that students' interest in physical education learning was still very low. The purpose of this study was to describe and obtain information about Increasing Interest in Learning of students in physical education through the application of demonstration learning methods in Class V SDN 04 Sungai Limau, Padang Pariaman Regency. This type of research is PTK which consists of four stages, namely planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subjects of the study consisted of 25 students of Class V SDN 04 Sungai Limau. The research data was collected using an observation sheet. Data were analyzed using percentages. The results of the study showed that the demonstration learning model could increase students' interest in learning in health education at SDN 04 Sungai Limau. Students' interest in learning from cycle I to cycle II. The learning interest of students in the first cycle was 70.66 (enough) to increase to 81.66 (good) with an increase of 11.00.